Development of fast and sensitive ultraviolet photodetector using p‐type NiO/n‐type TiO2 heterostructures. Issue 12 (20th October 2013) - Khun, K.; Ibupoto, Z. H.; Willander, M.
<x xml:space="preserve">Abstract</x> The fast and sensitive ultraviolet (UV) photodetector are of high demand due to their potential applications in several fields. Therefore, the present study describes the synthesis of well aligned TiO2 nanorods, NiO nanostructures and their composite hetero‐structures on the fluorine doped tin oxide (FTO) glass substrate by hydrothermal method. The material characterization was performed by scanning electron microscopy and X‐ray diffraction. The synthesized nanostructures are well aligned, dense, and uniform on the substrate. TiO2 nanostructures are tetragonal in shape with rutile phase. The current–voltage (I–V) characteristics were measured at room temperature. The photodiode exhibits nonlinear and rectifying behavior with high sensitivity and fast UV detection response. The enhanced photocurrent and less dark current are the attractive features of the fabricated photodiode. The observed UV response for the photodetector describes its worth and potential application in the respective fields. <inline-graphic xlink:href="ark:/27927/pgg3zmqk87q" content-type="pssa201330149-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />